Lake or Sea? The Unknown Future of Central Baltic Sea Herring - Dippner, Joachim W.; Fründt, Birte; Hammer, Cornelius (Frontiers in Ecology and Evolution, 2019)
The understanding of natural variability of harvestable fish stocks is of fundamental interest for their management; however, time series are often biased by the impact of fisheries. Observations show that the mean weight of central Baltic Sea herring (Clupea harengus), a quantity unbiased by fisheries, is indirectly influenced by the Atlantic Multi-decadal Oscillation (AMO) via a complex mediator chain, in which a transition from a marine to a freshwater state plays a major role. This observed trend is also projected for the future in regional climate change scenarios. The consequence of increasing precipitation is a reduction in the marine habitat, a change in the prey community and a decrease in the mean weight of three-year-old central Baltic Sea herring from 50-70 g in the late 1970s to 25-30 g today. The reduction in weight over this period represents a reduction in landings of approximately one million tons of herring and an economic loss of the order of €100 million.